Golden Venture Enterprise / Mohd Aziezul Izam Mohd Huda... [et al.] - Mohd Huda, Mohd Aziezul Izam; Saberi, Mohd Azwan; Abu Kasim, Khairul Syah; Abd Khadzi Zaini, Shah Rizal; Ali, Abdul Rahim (2000)
Golden Venture Enterprise is concentrated in Tiles services whether in supplying or in advising. They are involved in this type of business because they very confident about its market and potential in the future. It was a partnership business. They provide a service which by give an opportunity to customer to choose their own tiles to make them comfortable. This business located at Simpang Kuala, Alor Setar,Kedah.